Pengembangan Multimedia Animasi Berbasis Inkuiri untuk Meningkatkan Hasil Belajar Peserta Didik - Bintang, Andi; Danial, Muhammad; Ramlawati, Ramlawati (Program Pasca Sarjana UNM, 2019)
The purpose of this research is to produce inqury-based animated multimedia to improve chemistry learning outcomes in the reaction rate material, to find the quality of multimedia animation, and to find the responses given by both students and educators to the multimedia animation developed. The type of research used is Research and Development (R & D), with the type of Plomp Model where the Plomp development model consists of five stages, namely: (1) initial inevestigation stage, (2) design stage, (3) stage of realization, (4) the stage of testing, evaluation, and revision, (5) the implementation phase. The data analysis technique used in this research is a quantitative method using a questionnaire instrument student activity observation sheet, and Model Validation Sheet. The results of content validation were analyzed using Gregory method by using 2x2 Tabulations. Futhermore, the results of the evaluation of the contents of the interpretation of the multimedia feasibility of the animation developed. Multimedia quality produced by referring to Nieveen’s criteria, namely validity, practice,and effectiveness Based on the validation of expert validators and education practitioners as well as detailed trials that have been carried out shows that multimedia animation developed are considered appropriate to be used as media learning.